Interventions to reduce musculoskeletal disorders among motor vehicle workers: a review - Mohd Shafiei, Umi Kalsom; Karuppiah, Karmegam; Mohd Tamrin, Shamsul Bahri; Rasdi, Irniza; Alias, Ayuni Nabilah (American-Eurasian Network for Scientific Information, 2014)
Background: Musculoskeletal disorders (MSDs) are one of the most common work-related health problems affecting workers across all employment sectors. It causes problems in several economic activity sectors in industrialized countries. Objective: The purpose of this study was to identify which specific types of interventions were effective to reduce musculoskeletal disorders among motor vehicle workers. Results: Among of these studies, two of them were conducted in Netherlands and the other two also were conducted in the United State. The other five remaining articles were conducted in Japan, Finland, Italy, China and United Kingdom. All of them were intervention studies but only one of this was systematic review. In general, of the 9 included studies, 7 of the reviews showed positive effect from the implemented interventions done at their workplace. The 2 reviews presented that the interventions was not effective towards their workers. Conclusion: Overall, among several types of intervention used to reduce MSD, there is the most common type of intervention that usually applied towards motor vehicle workers which is administrative control intervention. However, this type of intervention is not effective as engineering control intervention which is provide more positive effects.